Effects of High Hydrostatic Pressure Processing and Supercritical Fluid Extraction on Bioactive Compounds and Antioxidant Capacity of Cape Gooseberry Pulp (Physalis Peruviana L.) - Romero-Figueroa, J (Elsevier B.V., 2018)
The aim of this study was to combine high hydrostatic pressure (HHP) and SFE-CO2 to extract bioactive compounds with antioxidant capacity (phenolics and β-carotene) from Cape gooseberry (Physalis peruviana L.) pulp. Extracts were evaluated immediately after processing by HHP at 300–400–500 MPa/1-3–5 min, respectively, and after 60 days of storage at 4 °C. Treatments at 300 MPa/1 min and 400 MPa/3 min showed an increase of antioxidant capacity compared to control untreated samples at day 0. Treatments at 500 MPa presented the highest antioxidant capacity (12388.3 μmol TE/100 g d.m.) after storage. Samples treated at 400 MPa/3 min presented a high content of total phenols at day 60. The highest β-carotene content was observed at 300 MPa/3 min (5.51 mg β-carotene/100 g d.m.). Our results indicate that HHP treatments combined with SFE-CO2 can promote active ingredient release in fruit matrices, increasing their bioactivities, as seen with antioxidant activity. © 2018